Compression for leg wounds. (1st August 2015) - Partsch, H.; Mortimer, P.
Summary: The main points in this scholarly review on the use of compression therapy in leg ulcers are the different modes of action of this treatment and the tools that are available including their practical applicability and use for self management. Due to its effect of counteracting gravity, compression is also suggested for ulcers with aetiologies that are not usually thought to require compression. The clinical evidence reported in ulcer‐healing studies are discussed and some considerations are made relating to the cost‐effectiveness of this management. In general, the failures of compression therapy are not caused by poor compression material but due to poor knowledge and application techniques of the care providers. Future studies comparing different compression devices should also report details concerning the compression material used and the pressure exerted.